Relating Hydro‐Mechanical and Elastodynamic Properties of Dynamically Stressed Tensile‐Fractured Rock in Relation to Applied Normal Stress, Fracture Aperture, and Contact Area - Wood, Clay E.; Manogharan, Prabhakaran; Rathbun, Andy; Rivière, Jacques; Elsworth, Derek; Marone, Chris; Shokouhi, Parisa (Journal of geophysical research. Solid earth, 2024)
We exploit nonlinear elastodynamic properties of fractured rock to probe the micro‐scale mechanics of fractures and understand the relation between fluid transport and fracture aperture under dynamic stressing. Experiments were conducted on rough, tensile‐fractured Westerly granite subject to triaxial stresses. We measure fracture permeability for steady‐state fluid flow with deionized water. Pore pressure oscillations are applied at amplitudes ranging from 0.2 to 1 MPa at 1 Hz frequency. During dynamic stressing we transmit ultrasonic signals through the fracture using an array of piezoelectric transducers (PZTs) to monitor evolution of interface properties. We examine the influence of fracture aperture and contact area by conducting measurements at effective normal stresses of 10–20 MPa. Additionally, the evolution of contact area with stress is characterized using pressure sensitive film. These experiments are conducted separately with the same fracture and map contact area at stresses from 9 to 21 MPa. The measurements are a proxy for “true” contact area for the fracture surface and we relate them to elastic properties using the calculated PZT sensor footprints via numerical modeling of Fresnel zones. We compare the elastodynamic response of the fracture using the stress‐induced changes in ultrasonic wave velocities for transmitter‐receiver pairs to image spatial variations in contact properties. We show that nonlinear elasticity and permeability enhancement decrease with increasing normal stress. Additionally, post‐oscillation wave velocity and permeability exhibit quick recoveries toward pre‐oscillation values. Estimates of fracture contact area (global and local) demonstrate that the elastodynamic and permeability responses are dominated by fracture topology. Plain Language Summary We perform laboratory experiments with fractured rock to understand the relation between fluid flow, fracture openness, and elastic properties under oscillating stresses. These experiments are conducted on rough, pre‐fractured granite specimens under normal stress conditions similar to those found in the shallow earth, a few kilometers in depth. Fluid pressure in the fracture is oscillated at various amplitudes at a fixed frequency. During this dynamic stressing, we use an ultrasonic device to monitor the evolution of the fracture interface. We examine the influence of fracture aperture and contact area by conducting measurements at increasing normal stress state. Additionally, the evolution of contact area with stress is characterized using pressure sensitive film, showing an image of where the two halves of the fracture are in contact. The ultrasonic monitoring reveals spatial variations in contact properties, which is informed by fracture contact area measurements. These measurements are also related to the fluid‐flow in response to dynamic stressing and similar comparisons are made for how the fracture interface evolves, recovers, following the stress perturbations. Key Points Lab experiments to simulate fracture processes under dynamic stressing Simultaneous measurements of fluid flow and elastic wave properties to quantify elastodynamic and hydraulic responses to dynamic stressing Local fracture aperture, not necessarily the stress state, dominates elastic and hydraulic responses to dynamic stressing